2018
DOI: 10.1016/j.arthro.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Editorial Commentary: Arthroscopic Hip Ligamentum Teres Reconstruction—Reality or Mythology?

Abstract: The ligamentum teres (LT) is perceived to contribute to hip stability and proprioception. LT incompetence can lead to pain and instability, which may play a role in chondral damage. Hip arthroscopy plays a role in diagnosing and treating LT tears. Reconstruction of the LT is feasible, but careful attention needs to be paid to tunnel positioning, graft material, graft length, and fixation methods. An anatomic femoral tunnel should exit at the fovea capitis on the femoral side, whereas the location for safe plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
(31 reference statements)
0
2
0
Order By: Relevance
“…The present study found favorable outcomes in patients with borderline dysplasia and LT tears using LT debridement only; however, LT reconstruction can be a valid option in select patients. 6,10…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The present study found favorable outcomes in patients with borderline dysplasia and LT tears using LT debridement only; however, LT reconstruction can be a valid option in select patients. 6,10…”
Section: Discussionmentioning
confidence: 99%
“…The present study found favorable outcomes in patients with borderline dysplasia and LT tears using LT debridement only; however, LT reconstruction can be a valid option in select patients. 6,10 There is a growing body of literature showing that LT reconstruction can successfully address LT dysfunction, particularly in patients with hip instability and generalized ligamentous laxity. To date, most of the available literature on LT reconstruction consists of technical articles, cadaveric or biomechanical studies, and small case series with short-term follow-up.…”
Section: Discussionmentioning
confidence: 99%